2023
DOI: 10.1079/cabireviews.2023.0004
|View full text |Cite
|
Sign up to set email alerts
|

Plant adaptability to climate change and drought stress for crop growth and production

Abstract: Abiotic factors pose a significant constraint for food security and agricultural production worldwide, and the issue has been exacerbated by extreme and rapid climate change. Heat and drought are the most important limiting factors that have a significant influence on crop growth and production. For better management, it is critical to understand the biochemical, ecological and physiological responses to these stresses. Plant responses to these challenges may be divided into three categories: phonological, phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…It has been reported that significant differences in chlorophyll pigment content occur in plants exposed to drought stress (Güzel, 2006). The decrease in chlorophyll content in plants under drought stress may be due to the degradation of chlorophyll (Christ et al, 2014) or changes in enzymatic activities involved in chlorophyll synthesis that slow or inhibit chlorophyll synthesis (Cotrina Cabello et al, 2023). In our study, drought stress caused a 15.2% decrease in leaf chlorophyll content compared to the control.…”
Section: Effects Of Humic Acid On Physiological Stress Indicatorsmentioning
confidence: 50%
“…It has been reported that significant differences in chlorophyll pigment content occur in plants exposed to drought stress (Güzel, 2006). The decrease in chlorophyll content in plants under drought stress may be due to the degradation of chlorophyll (Christ et al, 2014) or changes in enzymatic activities involved in chlorophyll synthesis that slow or inhibit chlorophyll synthesis (Cotrina Cabello et al, 2023). In our study, drought stress caused a 15.2% decrease in leaf chlorophyll content compared to the control.…”
Section: Effects Of Humic Acid On Physiological Stress Indicatorsmentioning
confidence: 50%
“…Similarly, other physiological parameters such as YII, ETR, PSR and Ft were also improved considerably. Improvement in intracellular enzymatic activities due to biostimulants and composting increase the uptake of essential nutrients leading towards the enhancement of chlorophyll production (Hamid et al, 2021;Cotrina Cabello et al, 2023;Younas et al, 2022;Gondal et al, 2023a). Chemical factors like organic carbon, organic matter, N, K, Zn, and P all got better when cytokinin and composting were used as a treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Priming, achieved through pre-exposure of plants to an elicitor or mild stress, induces a stress memory in plants and prepares them to be more effective in responding to subsequent stress events (Yuan, et al 2023). Priming is a promising strategy to enhance crop tolerance to different abiotic and biotic stress under climate change (Awaad and Awaad 2022;Cotrina Cabello, et al 2023). ABA has been for priming for enhanced drought tolerance in different plant species including Arabidopsis, pepper, tomato, apple, crab apple, and olive trees (Ban, et al 2017;Jakab, et al 2005 Small RNAs (sRNAs) are short non-coding RNAs with a length ranging between 20 and 24 nucleotides.…”
Section: )mentioning
confidence: 99%